2010
DOI: 10.5408/1.3544298
|View full text |Cite
|
Sign up to set email alerts
|

The InVEST Volcanic Concept Survey: Exploring Student Understanding About Volcanoes

Abstract: Results from the Volcanic Concept Survey (VCS) indicated that many undergraduates do not fully understand volcanic systems and plate tectonics. During the 2006 academic year, a ten-item conceptual survey was distributed to undergraduate students enrolled in Earth science courses at five U.S. colleges and universities. A trained team of graders scored 672 completed surveys, coding responses to each item with a score, out of 3, based on accuracy and comprehensiveness. Questions requiring only basic content knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Only 38% of our respondents correctly answered choice B. This item appears to be working as anticipated and consistent with research reported by Parham (2010) and colleagues. They created the 10-item student-supplied-response Volcanic Concept Survey and administered it to 672 students across five universities.…”
Section: Eggs Concept 5: Fossils Provide Evidence About the Types Of supporting
confidence: 92%
“…Only 38% of our respondents correctly answered choice B. This item appears to be working as anticipated and consistent with research reported by Parham (2010) and colleagues. They created the 10-item student-supplied-response Volcanic Concept Survey and administered it to 672 students across five universities.…”
Section: Eggs Concept 5: Fossils Provide Evidence About the Types Of supporting
confidence: 92%
“…Therefore, it was necessary designing a simulation media that was able to accommodate the students' requirement in learning about geosciences concept interactively as an effort to encourage geoscience skills [3]. Many volcanic simulation programs have been developed by geoscience educators and researcher at the international level, including Computer Aided Instruction or CAI [3], Interactive Virtual Earth Science Teaching or InVest [4], Vhub [5], MIAVITA [6]. These programs proved able to support the community to understand the phenomenon of the volcano but it must be modified and adapted according to the physics students need in order to improve geoscience knowledge and predicting skills based on volcanic activity in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to V-Volcano, a group from Iowa State University [1] [2], developed the Interactive Virtual Earth Science Teaching (InVEST) Volcanic Concept Survey to look into the prevalence and nature of the misunderstandings and alternate conceptions about volcanoes among first year geoscience students. Five universities were included in the study: Iowa State University, University of Texas El Paso, University of Georgia, Western Washington University, and Fort Valley State University.…”
Section: Introductionmentioning
confidence: 99%
“…The results from these surveys were analyzed, with the goal of identifying areas where introductory geology students were lacking or mistaken in their knowledge of volcanoes [1] [2]. The following four main misconceptions about volcanic formation were identified:…”
Section: Introductionmentioning
confidence: 99%